2009
DOI: 10.1037/a0015851
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of executive function deficits in mild cognitive impairment.

Abstract: Impairment in executive cognition (EC) is now recognized as relatively common among older persons with mild cognitive impairment (MCI), and may be predictive of the development of dementia. However, both MCI and executive functioning are broad and heterogeneous constructs. The present study sought to determine whether impairments in specific domains of EC are associated with specific subtypes of MCI. 124 MCI patients were divided into four subgroups (amnestic versus nonamnestic, and single-versus multiple-doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
171
4
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(198 citation statements)
references
References 94 publications
(98 reference statements)
17
171
4
6
Order By: Relevance
“…The results of this study show that decreases in both COWAT-FAS and Category Fluency performance can occur in individuals with single-domain aMCI when compared to CN individuals, which is consistent with previous research [9,13,14,15]. Despite the statistically significant differences and the impressive effect sizes, it is important to note that these differences were not found on a clinical level.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The results of this study show that decreases in both COWAT-FAS and Category Fluency performance can occur in individuals with single-domain aMCI when compared to CN individuals, which is consistent with previous research [9,13,14,15]. Despite the statistically significant differences and the impressive effect sizes, it is important to note that these differences were not found on a clinical level.…”
Section: Discussionsupporting
confidence: 77%
“…animal naming) may be indicative of single-domain aMCI [12,13,14,15]. Some of these studies also found statistically significant decreases in letter fluency performance among those categorized as single-domain aMCI [9,13,14]. Although statistically significant differences in letter and semantic fluency were found in these studies, the extent to which these measures add diagnostic value in identifying single-domain aMCI was not determined.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…29, No. 4, pp 437-445 areas (Pillon et al 2003) instead of a reduced choline acetyltransferase activity in temporal and frontal lobes yielding episodic memory and executive impairment in aMCI+ patients developing AD (Brandt et al 2009;Reinvang et al 2012). Interestingly, despite slow psychomotor speed and resting tremor that may interfere with performance in tests requiring motor abilities such as TOL, PD-MCI patients do not show lower performances than aMCI+ in this test.…”
Section: Discussionmentioning
confidence: 99%
“…WM is one of the most severely impaired cognitive functions in AD, outside of the characteristic episodic memory deficit [10,11,12,13]. Impairment in WM is also evident in MCI [14,15]. The few fMRI studies of WM in MCI have produced variable results, with both increased and decreased brain activity being reported [16,17].…”
Section: Introductionmentioning
confidence: 99%